2009, No. 4, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Rasa Zabarauskaitė, Poverty line calculation in the middle-income countries: methodological approach, 9Romualdas Valkauskas, Factorial index analysis in the research of change in expressions, 17Kirilas Kundušas, Živilė Simonaitytė, International financial reporting standards and USA accounting principles: main differences,  their causes and convergence, 25Monika Juonytė, Inga Galvanauskaitė, 7th International Financial Reporting Standard‘s „Cash Flow Reports“ and 5th Business Accounting Standard‘s „Cash Flow Report“ comparative analysis, 37Anastasija Jankauskaitė, Vilma Jelisejevaitė, Business combination accounting, 52Dainius Masiulevičius, Rasa Aleliūnaitė, Comparative analysis of 19th business accounting standard „Provisions,  contingent liabilities,  and contingent assets and events after the balance sheet date“ and 37th international accounting standard „Provisions,  contingent liabilities,  and contingent assets“, 66Eglė Grūnovaitė, The impact of currency exchange rate difference on financial results, 82Jokūbas Leipus, Gilmintas Albertavičius, Financial institutions of Islamic countries and their accounting features, 92Marija Kučinskienė, Asta Fominienė, The benefit of business incubators when stimulating the development of small and medium enterprises, 102Daiva Raziūnienė, New accounting textbook, 113
Keywords: none